Investigation of the Effects of Steam Injection on Equilibrium Products and Thermodynamic Properties of Diesel and Biodiesel Fuels - Jean Paul Gram Shou; Marcel Obounou; Timoléon Crépin Kofané; Mahamat Hassane Babikir (Journal of Combustion)
The effects of steam injection on combustion products and thermodynamic properties of diesel fuel, soybean oil-based biodiesel (NBD), and waste cooking oil biodiesel (WCOB) are examined in this study by considering the chemical equilibrium. The model gives equilibrium mole fractions, specific heat of the exhaust mixtures of 10 combustion products, and adiabatic flame temperatures. The results show that the mole fractions of carbon monoxide (CO) and carbon dioxide (CO2) decrease with the steam injection ratios. Nitric oxide (NO) mole fractions decrease with the steam injections ratios for lean mixtures. The specific heat of combustion products increases with the steam injection ratios. The equilibrium combustion products obtained can be used to calculate the nonequilibrium values of NO in the exhaust gases using some existing correlations of NO kinetics.